Analisis kandungan proksimat Octopus cyanea dari perairan Nusa Tenggara Timur: Analysis of the proximat content of Octopus cyanea from the East Nusa Tenggara waters - Cindy Soewarlan; Lumban Nauli Lumban Toruan; Suprabadevi Ayumasari Saraswati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Octopus cyanea is widespread in the waters of East Nusa Tenggara, is sold in traditional markets, and is exported to Europe. O. cyanea is traded for consumption, however, there is no adequate nutritional information related to this organism in East Nusa Tenggara. This study aimed to determine the main nutritional content of O. cyanea in the form of water, carbohydrates, fat, protein, ash, and crude fiber. Octopus samples were obtained from fishermen's catches in Kupang Bay anchored in Pasir Panjang, Kupang City, and from Perumaan-Nangahale waters, Sikka Regency. Three samples were collected from different fishing trips at each location. Eight tentacles from each sample were cut, mixed, and crushed for nutrient content analysis. Proximate analysis included fat content using the Soxhlet method, protein content using the Kjeldahl method, and determination of water content, ash content, and crude fiber referring to AOAC. The results showed that the largest components of O. cyanea were water 70.79-74.36%, protein 13.55-18.41%, carbohydrates 5.44-6.37%, ash 2.23-3.43%, fat 2.20-2.22%, and crude fiber 1.51-2.54%. This information can be used by consumers to estimate the risk to certain health conditions. Additionally, it would be beneficial to foster preventive measures against quality degradation.